DUAL SITUATED LEARNING MODEL AS REMEDIAL TEACHING TO ACID-BASE MISCONCEPTIONS - Mela Yuliyanti; Sulistyo Saputro; Ashadi Ashadi (EDUSAINS, 2022)
The research aimed to determine whether or not there is an acid-base misconception using a three-tier multiple choice and the effectiveness of using DSLM in reducing these misconceptions. The research design is descriptive qualitative research with a case study approach. The sampling technique used purposive sampling so that the sample is a student of class XI MIPA 1 and XI MIPA 5. The data collection technique was through three-tier multiple-choice, learning with DSLM, and interviews. After the first TTMC test, the researcher conducted remedial teaching with DSLM to improve the acid-base misconception. The results of the research showed that as many as 29 of 61 students had misconceptions about different sub-concepts. Most of the students had misconceptions about such characteristics of acid-base solutions, acid-base theories, pH concepts, the strength of acids and bases, the electrolytes of acid and base solutions, and neutralization reactions. After the researcher did DSLM learning, there was a decrease in misconceptions from 48.14% to 27.02% (low-misconceptions category). It shows that DSLM can be enough effective strategy to reduce student misconceptions.